Application of “mosiac sign” on T2-WI in predicting the consistency of pituitary neuroendocrine tumors - Nie, Ding; Zhao, Peng; Li, Chuzhong; Liu, Chunhui; Zhu, Haibo; Gui, Songbai; Zhang, Yazhuo; Cao, Lei (Frontiers in Surgery, 2022)
Purpose： Tumor consistency is important for pituitary neuroendocrine tumors (PitNETs) resection to improve surgical outcomes. In this study, we evaluated the T2-WI of PitNETs and defined a specific T2-WI signaling manifestation, the "Mosaic sign," to predict tumor consistency and resection of PitNETs. Design： A retrospective review of MRI and tumor histology of 137 consecutive patients who underwent endoscopic endonasal resection for PitNETs was performed. Methods： The "Mosaic sign" was defined by the ratio of the tumor itself T2-WI signals， and characterized by multiple intratumor hyperintense dots. The degree of tumor resection was an assessment by postoperative MRI examination. The presence of the "Mosaic sign" was compared with patients' basic information, tumor consistency, tumor pathological staining, and surgical result. To determine whether the presence or absence of "Mosaic sign" could predict tumor consistency and guide surgical resection of tumors. Results： Statistical analysis showed that the consistency of the tumor and the degree of resection were correlated with the "Mosaic sign". In the 137 cases of T2-WI, 43 had "Mosaic sign", 39 cases had soft tumor consistency, and 4 were classified as fibrous, of which 42 were completely resected and 1 was subtotal resected. Of the 94 patients without "Mosaic sign", the consistency of tumor of 54 cases were classified as soft, the remaining 40 cases were fibrous, 80 cases were completely resected, and 14 cases were subtotal resected. Postoperative cerebrospinal fluid leakage occurred in 1 patient. The number of corticotroph adenomas in the group of "Mosaic sign " was higher, with the statistical difference between the two groups（P=0.0343）. Conclusions： The presence of the "Mosaic sign" in T2-WI may provide preoperative information for pituitary adenomas consistency and effectively guide surgical approaches.